IIUM Blue Light Hazard - Che Azemin, Mohd Zulfaezal; Ithnin, Mohd. Hafidz; Mohd Salleh, Mohd Hazimin; Ahmad, Norsham; Mohd Tamrin, Mohd Izzuddin (2021)
This database allows users to view the information on the protection levels provided by blue control lenses available in the market. The full database is currently available on Google Play (http://bit.ly/blue-light-iium)